Is home‐based HIV testing universally acceptable? Findings from a case–control study nested within the HPTN 071 (PopART) trial. Issue 6 (16th April 2018) - Sabapathy, K.; Mulubwa, C.; Mathema, H.; Mubekapi‐Musadaidzwa, C.; Schaap, A.; Hoddinott, G.; Hargreaves, J.; Floyd, S.; Ayles, H.; Hayes, R.; ,
Abstract: Objective: The HPTN 071 (PopART) trial is examining the impact of a package including universal testing and treatment on community‐level HIV incidence in Zambia and South Africa. We conducted a nested case–control study to examine factors associated with acceptance of home‐based HIV testing and counselling (HB‐HTC) delivered by community HIV‐care providers (CHiPs) in PopART intervention communities. Methods: Of 295 447 individuals who were offered testing, random samples of individuals who declined HB‐HTC (cases) and accepted HB‐HTC (controls), stratified by gender and community, were selected. Odds ratios comparing cases and controls were estimated using multivariable logistic regression. Results: Data from 642 participants (313 cases, 329 controls) were analysed. There were no differences between cases and controls by demographic or behavioural characteristics including age, marital or socio‐economic position. Participants who felt they could be open with CHiPs (AOR: 0.46, 95% CI: 0.30–0.71, P < 0.001); self‐reported as not previously tested (AOR: 0.64; 95% CI: 0.43–0.95, P = 0.03); considered HTC at home to be convenient (AOR: 0.38, 95% CI: 0.27–0.54, P = 0.001); knowing others who had accepted HB‐HTC from the CHiPs (AOR: 0.49, 95% CI: 0.31–0.77, P = 0.002); or were motivated to get treatment without delay (AOR: 0.60, 95% CI: 0.43–0.85, P = 0.004) were less likely to decline the offer of HB‐HCT. Those who self‐reported high‐risk sexual behaviour were also less likely to decline HB‐HCT (AOR: 0.61, 95% CI: 0.39–0.93, P = 0.02). Having stigmatising attitudes about HB‐HTC was not an important barrier to HB‐HCT uptake. Men who reported fear of HIV were more likely to decline HB‐HCT (AOR: 2.68, 95% CI: 1.33–5.38, P = 0.005). Conclusion: Acceptance of HB‐HTC was associated with lack of previous HIV testing, positive attitudes about HIV services/treatment and perception of high sexual risk. Uptake of HB‐HCT among those offered it was similar across a range of demographic and behavioural subgroups suggesting it was 'universally' acceptable.